Safe prognostication following cardiac arrest: The role of the pharmacokinetics of fentanyl in patients treated with targeted temperature management. (April 2020) - Baldwin, F.; Gray, R.; Boyd, O.; Waxman, D.; Patel, B; Allen, M.; Scutt, G.
Abstract: Background: Neurological prognostication following cardiac arrest (CA) is complex and sedative agents may significantly impair responses to clinical examination. This study investigates the elimination of fentanyl in patients treated with targeted temperature management (TTM). Methods: We measured the blood concentration of fentanyl in 23 post-cardiac arrest patients treated with TTM following discontinuation of continuous infusion. Fentanyl was discontinued when the patients were rewarmed to a temperature of 36–36.5 °C and a blood sample taken 12 h later. Measured concentrations were compared with predicted concentrations using population pharmacokinetic parameters. Variables likely to prolong half-life were analysed using a multivariate regression model. Results: We found a statistically significant difference between median measured and predicted concentrations (measured 0.93 μg/L [range 0.11–8.29 μg/L] vs. predicted 0.30 μg/L [range 0.16-0.59 μg/L]; p < 0.05). Univariate analysis identified a significant relationship between estimated fentanyl half-life and serum lactate concentrations (r = 0.45, p < 0.05). Multivariate linear regression identified two variables (SAPS score and genotype), which together were able to explain approximately 30 % of the variation in the population (adjusted R 2  = 0.3177, p = 0.0194). No significant relationships were found between fentanyl half-life and patients' clinical or biochemical variables or co-administration of drugs metabolized by cytochrome p450. Conclusions: There is marked variation in the clearance of fentanyl following continuous infusion during TTM after CA which correlates with illness severity, lactate concentration and genetic polymorphisms of the cytochrome p450 liver enzymes. Sustained presence of fentanyl may influence response to neurological examination at 12 h post discontinuation in patients receiving the drug as an infusion as part of TTM.